The Role Of Credit Analysis In Implementing Risk Management To Mitigate Npf In Financing Companies - Hasibuan, Jesman (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Finance companies are financial services companies that are full of risks. Implementation of risk management for non-bank financial services institutions is regulated in POJK no. 44 of 2020, and SEOJK No. 7 of 2021. As a finance company, PT. KB Finansia Multi Finance also implements risk management which covers all ongoing business activities. The implementation of risk management at the branch level is carried out by credit analysts under the supervision of the Branch Manager and Area Credit Manager. This research was conducted at the Bekasi branch using a qualitative descriptive approach, and collecting data by interviewing 5 related respondents. Research results show that credit analysts are the leading filter in implementing credit risk management, by performing 1. 5C + 1P analysis, 2. KYC, 3. CDD, the NPF of the Bekasi Branch in the last year was an average of 1.18% with the highest NPF of 2.67%. For risk mitigation, credit analysts carry out analysis based on the principle of prudence, conduct debtor visits, coordinate with the head collection to propose credit restructuring, as well as efforts to settle credit internally.